Effect of supplementation of saponin containing herbs on in vitro methane production under different feeding systems - SIDHU, A S; WADHWA, M (The Indian Journal of Animal Sciences, 2019)
This study was taken up to assess the effect of herbal feed additives [HFAs; kulthi (Dohichos biflorus), patha (Cissampelos pareria), aritha (Sapindus trifoliatus)] supplemented at 0â€“3% on DM basis of total mixed rations (TMR) on the in vitro methane production and nutrient fermentation in a 3 Ã— 4 factorial design. TMR with different roughage to concentrate ratio (R:C) of 80:20, 75:25, 70:30 and 65:35 on DM basis were formulated. The roughage portion was made up of wheat straw and maize green fodder in 70:30 ratio. The chemical analysis of HFAs revealed that aritha had the highest concentration of both water and methanol soluble saponins; and condensed tannins (Leucocyanidin). Patha followed by kulthi had the highest concentration of vitamin C, flavonoids, total phenols and true tannins. The digestion kinetic parameters revealed that with the increase in level of concentrate in the diet, irrespective of type and level of supplementation of HFAs, the lag phase for fermentation of diet decreased linearly. The data conclusively revealed that the best response with respect to net gas production (NGP), digestibility of nutrients, methane production, volatile fatty acid (VFA) production, ME availability and other fermentation parameters from TMRs with different R:C ratios was observed in kulthi and patha supplemented at the rate of 2% of TMR with R:C ratio of 65:35 on DM basis.